Studies on the Influence of Drying Shrinkage Test Procedure, Specimen Geometry, and Boundary Conditions on Free Shrinkage. (19th December 2017) - Menu, Bruce; Jolin, Marc; Bissonnette, Benoit
Abstract : Although considerable progress has been made in enhancing the use and interpretation of free ring shrinkage test, little is known about the impact of the test procedure, the specimen geometry, the surface area-to-volume (S/V) ratio exposed to drying, and the boundary conditions (sealing configuration) on the measured shrinkage. This paper highlights recent findings illustrating the influence of the test procedure, the S/V ratio exposed to drying, the geometry of specimen, and the boundary conditions. A series of experimental results are presented from free shrinkage on ring test specimens to illustrate that the test procedure can significantly influence the measured free shrinkage. A second series of experimental results are presented from specimens with different geometries and S/V ratio exposed to drying to illustrate that drying shrinkage is dependent on both the specimen geometry and the surface exposed to drying. Test results further show that, even for the same S/V ratio exposed to drying, shrinkage is strongly dependent on the specimen's geometry and boundary conditions.